Pengembangan Media Roda Putar (Rotar) pada Materi IPA Siswa Kelas V SD - Dyah Woro Kuntari; Ilham Arvan Junaidi; Imelda Ratih Ayu (Departement of Mathematics Education, 2023)
This research was conducted at Tenggulang Baru State Elementary School, Musi Banyuasin district, to find out the Development of Rotating Wheel Media (Rotar) in Science Material for Class V Elementary School Students. The problem in this research is that the media used is still not attractive and innovative. The purpose of this research is to describe the validity and practicality of the results of the development of rotary media in the subject matter of healthy food for class V SD. This type of research includes development research. The method used is the development research method or called Research and Development, and uses the ADDIE development model. The results of this development research have produced a product in the form of Rotar Wheel media in the Natural Sciences subject on the Human Digestive System. The results of the assessment of the questionnaire distributed to experts showed that linguists scored 73% in the practical category, media experts scored 83% in the very practical category, and material experts scored 62% in the practical category. This means that the media can be concluded that the validity of the results of the development of rotary media on Healthy Food Materials for class V SD is very valid. Furthermore, this practicality test is carried out by filling out a practicality questionnaire that has been given to students. Practical value criteria are 61-80 Practical 81-100 Very Practical. Based on the results of the questionnaire given to students was 76%, this shows that the Rotar Wheel media is declared practical.